لغة الخطاب الحجاجي في الحديث النبوي من منظور تداولي صحيح مسلم أنموذجا - شحري، محمد البخيت سعيد حصون
This study highlights prophetic discourse`s argumentative language from a deliberative perspective in the Sahih of Imam Muslim. One of the most important objectives of this study: highlighting the deliberativeness of the concept, genesis and development and its relationship with the argument, and showing the concepts, types, types and features of argument, and its rooting in the ancient and modern Arab heritage, and also aimed at highlighting the argument's linguistic and rhetorical dimension of prophetic discourse and its authority in persuasion. This study investigated a series of prophetic hadiths to illustrate the argument and persuasive mechanisms that included the Prophet`s argument techniques (peace be upon him) to convey his message to the recipients, whether they are his companions or all Muslims of all time. This study has several conclusions, most notably: the Arabic and Western rhetoric is closely related to both arguments and trading, and it serves as a common area between them as a tool for understanding, influence and grooming. On the other hand, the graphic images present in the prophetic discourse of analogy and metaphor have many argument dimensions. This contributes to attracting the recipient, directing him towards the result to be convinced, and choosing the method of questioning or command is originally an argument choice. The objective is to choose the appropriate linguistic construction to influence the recipient and promote him to act or abandon, at the level of thought, behavior, and belief. The Prophetic hadith arguments were present in all subjects such as worship, transactions, ethics, literature, tazkiyah and others. Verifying and accepting Hadith, has indicated that arguments are an authentic approach rooted in the prophetic discourse.